Different types of guarantee schemes and their usage in safeguarding against default risks in international commercial practice. Issue 5 (12th September 2016) - Mugarura, Norman
Abstract : Purpose: The purpose of the paper is to examine the law relating to different types of guarantee schemes and the circumstances in which they are used to safeguard against default risks in international commercial practice. Different types of guarantee schemes are used in different contexts, often depending on which types and the purpose they have been sought. Design/methodology/approach: The paper was undertaken by evaluating secondary data sources, empirical examples and case law to underscore the pitfalls commercial parties need to always bear in mind with regard to guarantees and factoring and their usage in international commercial practice. Findings: The paper articulates the law relating to different types of guarantees and how they are harnessed to provide security against default risks in international commercial practice. By the very nature of guarantees, they tend to be in high demand in times of economic uncertainties when banks and other financial institutions find it less prudent to lend to borrowers without ensuring some form of security against potential defaults. Research limitations/implications: There are many different types of guarantee schemes clients can always opt for, but some of them are never written about as much. There is therefore limited data available to inform policy decisions by those who seek to use them. Lack of adequate information on any financial produces, leave alone guarantees, is not good for businesses and the public in terms of how to safeguard against risks inherent in usage and practice of guarantees. In this similar respect, there were not enough data available to evaluate the varied context in which guarantees are used. Practical implications: There are limited data available on guarantees, and because they are speciality products, the way they are used in practice can never be overlooked. It was necessary to publish this paper not only to address the foregoing need but also to discuss different types of guarantees and enhance understanding on their usage and practice. The paper articulates the law relating to guarantees and what guarantors need to always bear in mind before they accept to sign contracts of guarantees. Social implications: Guarantees are important for markets to operate efficiently. Their usage and practice has wide implications for various stakeholders such as banks, businesses, economies, governments and people, especially where contracts relating to them are not constituted and executed properly. Defaults on borrowed loans can lead banks not to lend money to businesses and subsequently choke them of a source on which many depend. Originality/value: This is the first paper that articulates the close relationship between guarantees, factoring and trusts. The paper has articulated the varied contexts in which each of the foregoing speciality products is harnessed in practice. Although this paper was written largely by reviewing and internalizing secondary data sources, it was done in a distinctive way to underscore the objectives it was written to achieve.